A CHECKLIST OF MICROALGAE IN THE FRESHWATER LAKES OF SOUTHERN BANGALORE (KAR) AND HOSUR (T.N) BORDER, INDIA - VIDYA PADMAKUMAR; THARAVATHY N. C. (The Bioscan, 2019)
A checklist of freshwater microalgae from the Southern Bangalore-Hosur border region was compiled. The studies included 4 major lakes and 2 smaller ponds of the area and conducted seasonally in sessions for a period of 2 years, from May 2017 to May 2019. The investigations resulted in the documentation of a large variety of algal communities and the discovery of the presence of one new species, Pseudokirchneriella subcapitata, which has never been recorded or documented in the past from India. A total of 119 species of algae were recorded. The maximum species were identified under class Cyanophyceae (47 taxa) followed by Bacillariophyceae (42 taxa), Chlorophyceae (23 taxa), Euglenophyceae (6 taxa), and Xanthophyceae (1 taxa).